2020
DOI: 10.1007/s00592-020-01517-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of educational attainment on the occurrence of gestational diabetes mellitus in two successive pregnancies of Finnish primiparous women: a population-based cohort study

Abstract: Aims To assess the impact of educational attainment on the occurrence and recurrence of gestational diabetes mellitus (GDM) in two successive pregnancies in primiparous women. Methods This is a population-based observational cohort study including all 2347 Finnish women without previously diagnosed diabetes, aged ≥ 20 years from the city of Vantaa, Finland, who gave birth to their first and second child between 2009 and 2015. National registries provided data on study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
(78 reference statements)
0
5
1
Order By: Relevance
“…However, this study did not yield the same findings (Table 1). In some previous studies, greater maternal weight gain 15,26 or BMI 27 during the first pregnancy was associated with recurrent GDM, whereas in two other previous studies, greater maternal weight gain between the pregnancies was associated with recurrent GDM 23,28 . In our study, greater maternal weight gain during the first pregnancy and the changes in body weight between the pregnancies were not predictors of recurrent GDM (Table 1).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…However, this study did not yield the same findings (Table 1). In some previous studies, greater maternal weight gain 15,26 or BMI 27 during the first pregnancy was associated with recurrent GDM, whereas in two other previous studies, greater maternal weight gain between the pregnancies was associated with recurrent GDM 23,28 . In our study, greater maternal weight gain during the first pregnancy and the changes in body weight between the pregnancies were not predictors of recurrent GDM (Table 1).…”
Section: Discussioncontrasting
confidence: 50%
“…In previous studies, older maternal age in index pregnancies, 4,14–20 higher prepregnancy maternal BMI 4,13,14,16,21–23 in index pregnancies, and higher prepregnancy maternal weight or BMI in subsequent pregnancies 24,25 were risk factors for recurrent GDM. However, this study did not yield the same findings (Table 1).…”
Section: Discussionmentioning
confidence: 85%
“…In another study, Rönö et al estimated a GDM prevalence of 13.0% in first the pregnancy, and 17.6% in the second pregnancy. GDM recurrence rate was 62.8% [ 184 ]. Ellenberg et al, analyzing data from the Hospital Discharge Register and the Finnish Medical Birth Register in the years 2006–2008 and 2010–2012 found an increase in GDM incidence from 7.2% to 11.2% [ 185 ].…”
Section: Europementioning
confidence: 99%
“…At the end of the study, 65 women of those who completed the LSI, developed GDM for a frequency of 13.1%; 36 women had recurrent GDM for a frequency of 24.5% for recurrent GDM, 29 women had new GDM for a frequency of 8.3%. The reported frequency of GDM after 4-m preconception LSI was favorably reduced in comparison to that reported in literature; wherein, Rönö et al [28] found the frequency of new GDM was 13% and 17.6% in the first and second pregnancies and the recurrence rate of GDM was 62.8%. Also, Egan et al [29] identified a GDM recurrence rate of 47.6%, and Morikawa et al [30] found the GDM recurrence rate among women who had GDM in the first and second pregnancies was 66.7%.…”
Section: Discussionmentioning
confidence: 58%